Determination of shareholders’ welfare with financing quality as a moderating variable - Husnadi, Tengku Chandra; Marianti, Tatik; Ramadhan, Tarisya; Husnad, Tengku Chandra (APTISI Transactions on Management (ATM), 2022)
The purpose of this study was to analyze the factors that might affect the shareholder welfare ratio (ROE). These factors include independent variables consisting of financing distribution ratio (FDR), low-cost funds ratio (CASA), net operating margin ratio (NOM), expense-based income ratio (FIR), and Financing Quality ratio (NPF). Furthermore, to determine the relationship of Islamic bank performance indicators on shareholder welfare with the ROE ratio indicator, NPF is a moderate variable. The method used to analyze the holder's welfare ratio (ROE) is moderate regression analysis with the error error model (ECM). The research sample used is the entire research population, namely monthly data from the Islamic banking industry for the period 2012-2020 (consisting of 14 Islamic commercial banks and 20 Islamic business units). The results of this study note that in the long run: FDR has a positive and significant effect on the ROE ratio, the NOM ratio has a negative and significant effect on the ROE ratio. While the variables of CASA ratio, FIR ratio and NPF have no effect on the ROE ratio. Furthermore, the NPF Moderating Variable strengthens the relationship of all direct and significant variables with the Shareholder Welfare Ratio (ROE), namely NPF moderates the negative and significant effect of FDR on the ROE ratio, NPF moderates the positive and significant effect of the ratio. on the ROE ratio. Furthermore, other variables NPF Moderating Casa and FIR have no effect on the ROE ratio. For the short term: FIR has a positive and significant effect on the ROE ratio, the NOM ratio has a negative and significant effect on the ROE ratio. While the FDR ratio, CASA ratio and NPF ratio variables have no effect on the ROE ratio. Furthermore, the NPF variable strengthens the relationship of all variables directly and significantly to the Shareholder Welfare Ratio (ROE), namely NPF moderates the negative and significant effect of FIR on the roe ratio, NPF moderates the positive and significant effect of the ratio. on the ROE ratio. While other variables, moderate NPF, FDR and CASA, have no effect on the ROE ratio. The implication of this study is to measure the welfare of shareholders, in this case the performance of Islamic banks with the ROE ratio approach. Why is the welfare ratio of all shareholders (ROE) important, because in accordance with the existence of Islamic banks it aims to provide benefits (maslahah) for the ummah. Islamic banks in carrying out their mandate have a commitment to be able to provide expectations from shareholders in the company and be able to develop products that are in accordance with the wishes and needs of customers. So from this study it can be said that of the 5 variables that affect the price. financing distribution ratio (FDR), low cost funds ratio (CASA), net operating margin ratio (NOM), cost-based income ratio (FIR) and Financing Quality ratio (NPF).